Patterns of emotional attachment and its relationship to cognitive distortions among students of An-Najah National University - Abu Helal, Yasmin Hasan (Journal of Educational and Psychological Sciences, 2020)
The objective of the research was to investigate the patterns of emotional attachment and its relation to the cognitive distortions of An-Najah National University students. It also aims to detect differences in emotional attachment patterns and cognitive distortions due to variables: Gender, Birth order. The researcher used the descriptive Correlative approach in the conduct of the study, Emotional attachment patterns scale, cognitive distortions scale were used to reach their outcomes, The study sample consisted of (280) students from An-Najah National University, The results indicated a positive correlation between the anxiety pattern and the cognitive distortions, the negative correlation between the safe pattern and the cognitive distortions, and the absence of a correlative relationship between the avoidance pattern and cognitive distortions, The results also showed There were differences in the pattern of anxiety due to gender, and there were no differences in emotional attachment patterns due to birth order, It also showed differences in cognitive distortions due to gender, and the absence of differences in cognitive distortions due to the birth order of students at An-Najah National University, The researcher recommended implementing awareness programs for mothers about emotional attachment patterns and their impact on their children in the future.